2, 4-D and dicamba removal from the surface of plastic mulch using overhead irrigation: analytical analysis and cucurbit bioassay crop response. (21st August 2021) - Hand, Lavesta C.; Eason, Kayla M.; Randell, Taylor M.; Grey, Timothy L.; Culpepper, A. Stanley
Abstract: Glyphosate and paraquat are effective preplant burndown herbicide options for multicrop vegetable production that uses plastic mulch, but problematic weeds such as wild radish, cutleaf evening primrose, annual morningglory, or horseweed may not be adequately controlled with these herbicides alone. The herbicides 2, 4-D and dicamba could help control these troublesome weeds prior to planting if they can be removed from plastic mulch and thus avoid crop damage. Treatments included 2, 4-D (1, 065 and 2, 130 g ae ha −1 ) and dicamba (560 and 1, 120 g ae ha −1 ) applied broadcast over plastic mulch a day before transplanting. Just before transplanting, treatments received either 0.76 cm of water via overhead irrigation or no irrigation. Plastic mulch samples were collected at application and planting to determine herbicide presence using analytical techniques, and cantaloupe and zucchini squash were subsequently transplanted on the plastic beds. Analytical ultra-high performance liquid chromatography revealed that 88% to 99% of the initial herbicide concentration was present at crop planting when irrigation was not implemented. At most, a 1/50 rate of dicamba and a 1/500 rate of 2, 4-D was present at planting when overhead irrigation was applied prior to transplanting. Maximum cantaloupe and squash injury from 2, 4-D with irrigation was 10% and did not influence plant growth, biomass, or yield. For dicamba with overhead irrigation, cantaloupe injury was 35%, vine lengths were reduced by 24%, and maturity was delayed, whereas squash injury ranged from 9% to 12%, with no influence on growth or yield. Without irrigation to wash herbicides from the mulch prior to planting, 60% to 100% injury of both crops occurred with both herbicides. Zucchini squash was more tolerant to dicamba than cantaloupe. Results demonstrated that 2, 4-D can be adequately removed from the surface of plastic mulch with irrigation, whereas a single irrigation event was not sufficient to remove dicamba.